Strategic posturing of Malaysian mobile phone service providers - Said, Mohd Fuaad; Adham, Khairul Akmaliah; Quoquab, Farzana (Universiti Putra Malaysia Press, 2013)
The Malaysian mobile phone service started with only one service provider in the 1980s, which then increased to seven by mid 1990s due to government liberalization policies. Nonetheless, this number decreased to three in 2004, and this marked the beginning of an intense competition within the industry. Utilizing the case study and content analysis methodologies, we gathered data from the public domain and developed a case that describes strategic actions taken by members within the industry. Based on Miles and Snow's business strategy typology, we analyzed the case data by answering the questions of "How do the industry players compete?", and "What factors are important in shaping their strategies?" The research objective is to provide a conceptualization of strategic posturing by Malaysian mobile phone service providers. Our analysis show that the initial strategic moves of these companies are predominantly prospecting, and, later, analyzing, when the market reaches subscription saturation, and competition begins to intensify. Industry latecomers either arise as challengers or adopt a niche strategy as their strategic option. The adaptive actions of these companies are greatly influenced by institutional elements of the government's policies, market situation, and rivals' actions and responses. These actions are mainly tied to resources and capabilities of their large internationalized parent companies. Taken altogether, the perspective of adaptation, as well as the theories of organizational ecology and institutionalization, provides important theoretical grounds in explaining strategic posturing and factors that influence it.